Maternal and Fetal Outcome Where Three Doses of Prostaglandin E2 were Used for Induction of Labour (Journal of Fatima Jinnah Medical University, 2018)
Objective: To assess maternal and fetal outcomes where three doses of vaginal prostaglandins (PGE2) are used for induction of labour. Subjects and Methods: This study was Retrospective cohort study conducted in Gynae B unit LRH from 1st January 2013 till 28th February 2014. A total of 708 patients had induction of labour with prostaglandin E2, among them 65 women had received three doses of vaginal PGE2 (3mg tablet or 2mg gel) for induction of labour. The clinical record of these 65 patients was further analyzed. Primary outcomes included mode of delivery, frequency of hyperstimulation of uterus, postpartum haemorrhage (PPH), and fetal outcome was observed in terms of Apgar score. Results: In this study analysis of 65 patients who received third dose of prostaglandin E2 was done, it is observed that 58.46% (n=38) had normal vaginal delivery, while 36.92% (n= 24) had caesarean section, out of which 26.15% (n=17) caesarean sections were done for failure to establish labour after 3rd dose of prostaglandin E2, PPH occurred in 3.07% (n= 2) of patients while there was no case of uterine Hyperstimulation. It was observed that 92.30% (n=60) of babies were born with Apgar score of 7 or above. Conclusion: The delivery outcomes for those women receiving a third 3mg dose of PGE2 shows that just over 58.46% of these women achieve a vaginal delivery, and maternal and fetal outcome were also reassuring which suggests that use of 3rd doses of vaginal PGE2 for induction of labour can be considered in cases where labour is not established after two doses of PGE2, after maternal and fetal reassessment.
Keywords: Induction of labour, Prostaglandins E2